Scope and limitations of a multiplex conventional PCR for the diagnosis of S. stercoralis and hookworms - Fleitas, Pedro Emanuel (2021)
Objectives: Describe the diagnostic characteristics of a conventional multiplex PCR for the diagnosis of S. stercoralis, N. americanus and Ancylostomas spp. Methods: Fecal samples were collected from a cross-sectional study in Oran department, Salta province, Argentina. The stool samples were analyzed using concentration-sedimentation, Harada Mori, McMaster, and Baermann techniques. DNA was extracted from 50 mg fecal sample using the FastPrep Spin Kit for Soil. Three pairs of primers were used for the amplification of three products of 101, 330, and 577 base pairs (bp) for S. stercoralis, N. americanus and Ancylostoma spp, respectively. The sensitivity and analytical specificity of multiplex PCR were evaluated, as well as the sensitivity and diagnostic specificity, using a composite standard and Bayesian approach. Results and Conclusions: Multiplex PCR did not present cross-reaction with other intestinal parasites, and the detection limit for multiplex PCR was between 2 and 20 pg of genomic DNA. In addition it presented a diagnostic sensitivity of 97.4% for S. stercoralis and 90.3% for hookworms with a specificity of 100% and 87.6%, respectively. PCR identified a higher proportion (p <0.01) of coinfections (15.3%) than microscopic techniques (3.5%). Also, multiplex PCR showed that there was a positive association between S. stercoralis and hookworms (odds ratio = 2.12). However, this association was due to N. americanus (odds ratio= 3.22), since no association was observed between S. stercoralis and Ancylostoma spp. Neither was an association observed between the two species of hookworms.